Economics of Vices and VirtuesInternational - Denis Kadochnikov; Danila Raskov (Journal of Economic Sociology, 2015)
The International Academic Conference on Economics of Vices and Virtues was held at Faculty of Liberal Arts and Sciences of the St. Petersburg State University on May 15–16, 2015. The conference, organized by the Center for the Study of Economic Culture, was the fourth in a series of conferences aimed at a comprehensive discussion of the complex issues related to economic culture and to the interaction of cultural values, economic activities and economic science. Researchers from various regions of Russia, as well as from Belarus, Kyrgyzstan, US, Belgium, Italy, Finland attended the conference. Among key topics of the conference were issues of theoretical and methodological reflection on the concepts of vices and virtues in the context of social sciences and humanities, as well as public policy concerns in regards to what traditionally is measured using these concepts. Primary attention was paid to the issues of alcohol consumption and alcohol policy in Russia and other countries, including issues of formation of drinking practices and the tools that governments can use to influence them. The conference participants also discussed other cultural practices whose perception as “vicious” or “virtuous” by the general public and by social scientists may differ.